(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The objective and primary mirror of language growth and change is its vocabulary, any changes in society, large or small, are reflected, first and foremost, precisely at this lexical level. This article also analyzes research on the lexical and lexicographic features of the dastans of Ergash Jumanbulbul ugli.